Galilei in vprašanje o uglasitvi - Sukljan, Nejc (Muzikološki zbornik, 2012)
The article discusses the tuning question as exposed in Vincenzo Galilei's treatise Dialogo della musica antica et della moderna, the author being one of the main 16th century Italian music theorists. His first attempt to determine the musical acoustic system of his time is presented, along with Galilei's critical approach and his attempt to set a new system, which he presents in the case of lute tuning.
Keywords: Galilei, Vincenzo, 1520-1591; Galilei, Vincenzo: Dialogo della musica antica et della moderna; glasbeni sistemi; music theory; musical systems; Renaissance; renesansa; teorija glasbe; tuning; uglasitev